2004
DOI: 10.1124/jpet.103.063347
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Chemoprotection without Compromise of Chemotherapy Efficacy in a Rat Brain Tumor Model

Abstract: Thiol chemoprotective agents can reduce chemotherapy side effects, but clinical use is limited due to concerns of impaired chemotherapeutic efficacy. We evaluated whether an optimized bone marrow chemoprotection regimen impaired the efficacy of enhanced chemotherapy against rat brain tumors. Nude rats with intracerebral human lung carcinoma xenografts were treated with carboplatin, melphalan, and etoposide phosphate delivered intra-arterially with osmotic blood-brain barrier disruption (n ϭ 8/group). Thiol che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 15 publications
1
41
0
1
Order By: Relevance
“…As a result, there was a marked decrease in the need for hearing aids . The current results, together with previous in vivo tumor efficacy studies (Muldoon et al, 2000;Neuwelt et al, 2004), suggest that chemoprotection route and timing of administration can be manipulated to maintain CDDP antitumor efficacy while protecting against chemotherapy toxic side effects. As these studies used carboplatin instead of CDDP as in the current study, further in vivo experiments are necessary and underway to affirm the antitumor efficacy of CDDP in this model.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As a result, there was a marked decrease in the need for hearing aids . The current results, together with previous in vivo tumor efficacy studies (Muldoon et al, 2000;Neuwelt et al, 2004), suggest that chemoprotection route and timing of administration can be manipulated to maintain CDDP antitumor efficacy while protecting against chemotherapy toxic side effects. As these studies used carboplatin instead of CDDP as in the current study, further in vivo experiments are necessary and underway to affirm the antitumor efficacy of CDDP in this model.…”
Section: Discussionmentioning
confidence: 86%
“…Muldoon et al (2000) reported that delaying sodium thiosulfate (STS) for 8 h did not adversely affect its oncological activity but still offered protection from carboplatin-induced ototoxicity in a guinea pig model. Neuwelt et al (2004) demonstrated that the efficacy of chemotherapy for rat brain tumors was not affected by thiol chemoprotection. A clinical trial showed otoprotection after carboplatin increased with a longer delay of STS infusion ).…”
mentioning
confidence: 99%
“…In addition, enolate cytoprotection could stem the toxicity of drugs that are significant electrophiles, e.g., cisplatin, clopidogrel (Dedon and Borch, 1987;Singh et al, 2011). This suggestion is feasible, since electrophile-mediated toxicity can often be prevented without affecting the therapeutic (e.g., antineoplastic) efficacy of these drugs (Borch et al, 1980;Neuwelt et al, 2004). Finally, many environmental chemicals are electrophiles (e.g., acrolein, acrylamide, methylmercury) that produce toxicity as a consequence of acute or chronic exposure.…”
Section: Acetylcyclopentanone Prevents Acetaminophen Hepatotoxicitymentioning
confidence: 99%
“…Our previous studies demonstrated that NAC protects against alkylating chemotherapy cytotoxicity in vitro , blocks ototoxicity in rats treated with cisplatin (Dickey et al, 2004), and reduces chemotherapy-induced bone marrow toxicity in rats . We have found that thiol chemoprotection can be obtained without blocking the antitumor effects of chemotherapy (Muldoon et al, 2000;Neuwelt et al, 2004). Nonetheless, chemoprotectants have had relatively limited clinical use due to concerns of impaired antitumor efficacy.…”
mentioning
confidence: 99%